A study of thermal comfort perception to local residence of tropical country of Malaysia / Abdul Faiz Yusof - Abdul Faiz , Yusoff (2018)
The emphasis on field surveys from around the world, which focuses on hot and humid countries, enables us to understand thermal perception and evaluate outdoor thermal comfort conditions. Focusing on the thermal comfort perception level between individuals, it tries to explain how this influences the outdoor activities time and their actions to improve their comfort level at outdoor area. This research function is to identify the thermal comfort perception acceptance level, best condition for thermal comfort and future improvement of thermal comfort perception. Beyond acclimatization and behavioral adaptation, through adjustments in clothing and changes to the metabolic heat, psychological adaptation plays a critical role to ensure thermal comfort and satisfaction with the outdoor environment. Such parameters include recent personal experiences and expectations; personal choice and perceived control, more important than whether that control is actually exercised, and the need for positive environmental stimulation suggesting that thermal neutrality is not a pre-requisite for thermal comfort. This study has been done on cohort in Petaling Jaya. By using surveys form to verify the difference of thermal comfort perception between individuals. Different individual have different thermal comfort perception level. Some of it is due to physical difference, other either psychological difference. Thermal comfort level is varies but still have similarities for majorities of respondent. The consistent low correlations between objective microclimatic variables, subjective thermal sensation and comfort outdoors, internationally, suggest that the difference in individual thermal perception brings us to search for ideal outdoor thermal comfort perception.